Precise positioning in Europe using the Galileo and GPS combination - Kwaśniak, Dawid; Cellmer, Sławomir; Nowel, Krzysztof (International Conference “Environmental Engineering”, 2017)
For many years American GPS and Russian GLONNAS were the leading navigation systems widely used for navigation purposes. In recent years two new navigational systems have been developed. These systems are the European Galileo system and the Chinese BeiDou System. The full operability of both systems is foreseen for 2020. The full Galileo constellation will consist of 30 Medium Earth Orbit (MEO) satellites. In this paper the GPS and Galileo combination is used to obtain precise positions using the MAFA method. Results from GPS only and GPS+Galileo positioning are presented. In the test 11 Galileo satellites were used. The number of visible GPS satellites during the test was between 8 and 12. For Galileo the number of visible satellites was between 2 to 4, with 4 satellites visible for most of the day. Adding Galileo satellites to GPS reduces the PDOP factor value and improves the DGNSS and RTK results.
Keywords: GPS; Galileo; MAFA method; RTK